The Role Of Emotional Intelligence In Forming Stress Resilience - Tajiboyeva, Odinaxon (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
The article highlights the importance of emotional intelligence in forming a person’s stress tolerance. Emotional intelligence, as a person’s ability to understand and manage their own emotions and correctly perceive the emotions of others, is an important factor in psychological stability. The results of the study show that individuals with developed emotional intelligence choose positive adaptation strategies in stressful situations and maintain emotional stability.